Electrohydrodynamic deposition of polymeric droplets under low-frequency pulsation - Xu, Lei (Langmuir : the ACS journal of surfaces and colloids, 2011)
Circularly shaped polymeric droplets with diameter of about 20 μm have been intermittently ejected and deposited in an orderly manner on a collector from a syringe needle by means of near-field, electrohydrodynamic reactions using pulsating voltages at around 2.25 kV. The needle has an inner diameter of 100 μm and was placed 1 mm above a silicon conductor substrate to have location control for droplet depositions. Under low-frequency operation of less than 100 Hz, the deposition frequency of droplets, f(dep), has been observed to be equal to the frequency of the applied driving voltage divided by an integer, N, as small as 1. Furthermore, the diameter of the deposited droplets has been found to be linearly dependent on (Q/f(dep))(1/3), where Q is the polymer solution supply rate at around 30 nL/s. These experimentally observed droplet ejection rules under low-frequency pulsation provide useful design guidelines for controllable deposition of polymer droplets in various potential applications, including electrohydrodynamic printing